Negative electrode active material, method for producing negative electrode active material, negative electrode composition, negative electrode for lithium secondary battery comprising same, and lithium secondary battery comprising negative electrode

By using the rapid cooling process to form a plate-shaped silicon precursor in the production of the negative electrode active material of the lithium secondary battery, the silicon-based active material is pulverized and prepared, the problem of the silicon-based compound breaking the conductive path caused by volume expansion during charging and discharging is solved, and a higher battery capacity retention rate and stability of the conductive path are achieved.

CN119654713APending Publication Date: 2025-03-18LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480003624.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-30
Filing Date
2024-01-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, when using silicon-based compounds as the negative electrode active material, the volume expands rapidly during charging and discharging, resulting in the disconnection of the conductive path and deteriorating the battery characteristics.

Method used

By performing a rapid cooling process before metallurgical grade (MG)-Si crushing, a plate-shaped silicon precursor is formed, and a silicon-based active material is prepared by pulverizing the precursor, and its grain size and high-angle grain boundary ratio are adjusted.

Benefits of technology

This method can improve the circulation capacity retention rate and initial capacity efficiency of the lithium secondary battery, and prevent volume expansion from damaging the conductive path.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654713A_ABST
    Figure CN119654713A_ABST
Patent Text Reader

Abstract

Provided is a negative electrode active material containing a silicon-based active material, in which the silicon-based active material contains silicon-based crystal grains, the ratio of high-angle grain boundaries in the silicon-based crystal grains is 30% or more, and the silicon-based active material satisfies the following formulae 1 and 2: [Formula 1] 1m < = particle size of the silicon-based active material (D50) < = 10m [Formula 2] 2nm < = grain size of the silicon-based active material < = 1m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application is based on and claims the benefit of priority from Korean Patent Application No. 10-2023-0052006 filed on April 20, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Background Art

[0002] The present invention relates to a negative electrode active material, a method for producing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode.

[0003] Due to the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative or clean energy. As part of this, the most active research field is the field of power generation and storage using electrochemical reactions.

[0004] Currently, secondary batteries can be exemplified as a representative example of electrochemical devices using such electrochemical energy, and the fields of use thereof are gradually expanding.

[0005] With the technological development and demand increase of mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among these secondary batteries, lithium secondary batteries with high energy density and high voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as an electrode for high-capacity lithium secondary batteries, a method for manufacturing a high-density electrode with higher energy density per unit volume has been actively studied.

[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode contains a negative electrode active material through which lithium ions released from the positive electrode are embedded and deintercalated. As the negative electrode active material, silicon-based particles having a large discharge capacity can be used. Therefore, research is being actively conducted on the performance improvement of negative electrode active materials using silicon-based particles.

[0007] Prior art literature

[0008] (Patent Document 1) Japanese Patent Publication No. 2009-080971. Summary of the invention

[0009] Technical issues

[0010] As a result of research on reducing grain size, it has been confirmed through research that when the cooling rate is adjusted in a rapid cooling process before pulverizing existing metallurgical grade (MG)-Si, and then a plate-like silicon precursor is formed and pulverized, the target grain size can be reduced and the high-angle grain boundary ratio can be adjusted.

[0011] The present application relates to a negative electrode active material, a method for manufacturing the negative electrode active material, a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode.

[0012] Technical Solution

[0013] According to one embodiment of the present specification, a negative electrode active material including a silicon-based active material is provided. In the negative electrode active material, the silicon-based active material includes silicon-based grains, the high-angle grain boundary ratio in the silicon-based grains is 30% or more, and the silicon-based active material satisfies the following formulas 1 and 2.

[0014] [Formula 1]

[0015] About 1µm≤Particle size of silicon-based active materials (D50)≤about 10µm

[0016] [Formula 2]

[0017] About 2nm≤Grain size of silicon-based active materials≤about 1µm

[0018] According to another embodiment, a method for manufacturing a negative electrode active material is provided. The method for manufacturing a negative electrode active material comprises the following steps:

[0019] rapidly cooling the metallic silicon to form a silicon precursor; and

[0020] The silicon precursor is pulverized to form a silicon-based active material.

[0021] The step of rapidly cooling the metallic silicon includes melt spinning, suction casting or injection casting.

[0022] According to another embodiment, a negative electrode composition is provided, the negative electrode composition including the negative electrode active material according to the present application; a negative electrode conductive material; and a negative electrode binder.

[0023] According to another embodiment, a negative electrode for a lithium secondary battery is provided. The negative electrode comprises a negative electrode collector layer; and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode collector layer. The negative electrode active material layer comprises the negative electrode composition according to the present application or a cured product thereof.

[0024] In addition, a lithium secondary battery is provided, which includes: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0025] Technical Effects

[0026] Unlike conventional pulverization processing methods, the negative electrode active material according to one embodiment of the present invention is manufactured by performing a rapid cooling process before pulverizing metallurgical grade (MG)-Si to form a plate-like silicon precursor, and the grain size and high-angle grain boundary ratio of the silicon-based active material can be optimized by controlling the cooling rate.

[0027] As described above, by pulverizing a plate-like silicon precursor having nano-sized crystals, a silicon-based active material having nano-sized crystals can be obtained. Then, when the silicon-based active material is used to manufacture a negative electrode, the cycle capacity retention rate and the initial capacity efficiency are improved.

[0028] The negative electrode active material of the present invention contains one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2) as the silicon-based active material, and the content of SiOx (x=0) is about 70 parts by weight or more relative to 100 parts by weight of the silicon-based active material. For example, although pure Si active material is included, the problem of volume expansion caused by charge and discharge, which is a problem caused by pure Si active material, is solved by adjusting the grain size. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a flow chart of a process for producing a silicon-based active material according to one embodiment of the present application.

[0030] Figure 2 An enlarged view of a silicon-based active material according to one embodiment of the present application is shown.

[0031] Figure 3 : is a view showing a stacked structure of a negative electrode for a lithium secondary battery according to one embodiment of the present application.

[0032] Figure 4 is a view showing a stack structure of a lithium secondary battery according to one embodiment of the present application.

[0033] Figure 5 is a view showing a method of calculating the grain size.

[0034] Figure 6 It is a view showing the misorientation angle.

[0035] In some of the drawings, the same reference numerals are given to the same parts. It will be appreciated by those skilled in the art that the drawings simply and clearly depict the elements and are not necessarily drawn to scale. For example, to facilitate understanding of the various embodiments, the sizes of some elements shown in the drawings may be exaggerated compared to other elements in the illustrations. In addition, elements of the known art that are useful or basic in commercially feasible embodiments may not be depicted in general, in order not to interfere with the conception of the various embodiments of the present invention.

[0036] Reference numerals

[0037] 1 Silicon-based active materials

[0038] 2 Silicon-based grains

[0039] 3 Grain boundaries

[0040] 4 Orientation misalignment

[0041] 10 Negative electrode current collector layer

[0042] 20 Negative electrode active material layer

[0043] 30 Diaphragm

[0044] 40 Positive electrode active material layer

[0045] 50 Positive electrode current collector layer

[0046] 100 Negative electrode for lithium secondary battery

[0047] 200 Positive electrode for lithium secondary battery DETAILED DESCRIPTION

[0048] Before explaining the present invention, some terms are first defined.

[0049] In the present specification, unless there is specific description to the contrary, when it is said that a certain part “includes” a certain component, it means that the certain part may further include other components rather than excluding the other components.

[0050] In this specification, “p to q” means a range of “p or more and q or less”.

[0051] In this specification, "specific surface area" is measured by the BET method, specifically, it is calculated by the nitrogen adsorption measured at liquid nitrogen temperature (77K) by using BELSORP-mini II of BEL Corporation of Japan. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.

[0052] In this specification, "Dn" refers to particle size distribution, and refers to the particle size at n% point according to the cumulative distribution of the number of particles of particle size. That is, D50 is the particle size (average particle size) at 50% point according to the cumulative distribution of the number of particles of particle size, D90 is the particle size at 90% point according to the cumulative distribution of the number of particles of particle size, and D10 is the particle size at 10% point according to the cumulative distribution of the number of particles of particle size. On the other hand, the average particle size can be measured by using a laser diffraction method. For example, the powder to be measured is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). When the particle passes through the laser beam, the particle size distribution is calculated by measuring the difference in the diffraction pattern according to the particle size.

[0053] In one embodiment of the present application, the particle size or particle diameter may mean an average diameter or a representative diameter of individual grains constituting the metal powder.

[0054] In this specification, the meaning that a polymer contains a certain monomer as a monomer unit means that the monomer participates in a polymerization reaction and is contained in the polymer as a repeating unit. In this specification, when it is said that a polymer contains a monomer, it is interpreted in the same way that the polymer contains a monomer as a monomer unit.

[0055] In this specification, unless otherwise specified as a "homopolymer", "polymer" is understood to be used in a broad sense including copolymers.

[0056] In this specification, weight average molecular weight (Mw) and number average molecular weight (Mn) are polystyrene equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) with various degrees of polymerization as standard materials. The monodisperse polystyrene polymers are commercially available for molecular weight measurement. In this specification, unless otherwise specified, molecular weight means weight average molecular weight.

[0057] As used in this specification, "about," "approximately," and "substantially" are used to refer to ranges of numerical values ​​or degrees or their approximate values, taking into account inherent manufacturing and material tolerances, and to prevent an infringer from unfairly using the disclosed content, where reference is made to precise or absolute numerical values ​​that are provided to assist in understanding the present invention.

[0058] According to the recent demand for high-density energy batteries, a method for increasing battery capacity by using silicon-based compounds such as Si / C or SiOx together as negative electrode active materials is being studied. The capacity of the silicon-based compound is as high as ten times or more that of the graphite-based material. On the other hand, although the silicon-based compound as a high-capacity material has a large capacity compared with conventionally used graphite, the problem is that the volume expands rapidly during charging and the conductive path is disconnected, thereby deteriorating the battery characteristics.

[0059] Therefore, various studies are being conducted to solve the problems in using silicon-based compounds as negative electrode active materials. For example, a method of controlling the driving potential using silicon-based compounds as negative electrode active materials, a method of suppressing volume expansion itself such as a method of additionally coating a thin film on an active material layer, or a method of controlling the particle size of silicon-based compounds, or various methods for preventing disconnection of conductive paths are discussed, but each method has advantages and disadvantages.

[0060] On the other hand, in the case of Si negative electrode active materials, studies have shown that since the grain boundaries act as diffusion paths for lithium, the wider the grain boundaries, that is, the smaller the grain size, the more favorable the performance characteristics of the secondary battery. However, in the case of manufacturing negative electrode active materials by pulverizing metallurgical grade Si (MG-Si), since the general grain size of MG-Si ranges from several hundred microns to several millimeters, the grain size reduction of the Si active material is limited. Therefore, there are still limitations on the improvement of the performance characteristics of secondary batteries.

[0061] The present invention provides a technology that is capable of controlling the grain size of Si particles, for example, by reducing the grain size of Si particles to a size of several nanometers to tens of nanometers, thereby preventing the conductive path from being damaged due to the volume expansion of the silicon-based compound even when the silicon-based active material is used as a negative electrode active material to improve the capacity performance of a secondary battery.

[0062] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0063] According to one embodiment of the present specification, a negative electrode active material is provided. The negative electrode active material includes a silicon-based active material, and the silicon-based active material includes silicon-based grains. The high angle grain boundary ratio (HAGB) in the silicon-based grains is 30% or more, and the silicon-based active material satisfies the following formulas 1 and 2.

[0064] [Formula 1]

[0065] About 1µm≤Particle size of silicon-based active materials (D50)≤about 10µm

[0066] [Formula 2]

[0067] About 2nm≤Grain size of silicon-based active materials≤about 1µm

[0068] Unlike conventional pulverization methods, in the negative electrode active material according to one embodiment of the present invention, before pulverizing MG-Si, a rapid cooling process is performed to form a plate-shaped silicon precursor. As a result, it is possible to optimize the grain size and the high-angle grain boundary (HAGB) ratio of the silicon-based active material prepared by pulverizing the plate-shaped silicon precursor generated by adjusting the cooling rate.

[0069] As described above, a silicon-based active material having nanosized grains can be obtained by pulverizing a plate-shaped silicon precursor having nanosized grains. When the silicon-based active material is used to manufacture a negative electrode for a lithium secondary battery, the cycle capacity retention rate and the initial capacity efficiency of the lithium secondary battery are improved.

[0070] In one embodiment of the present application, the silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and relative to 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be about 70 parts by weight or more.

[0071] In one embodiment of the present application, the silicon-based active material contains SiOx (x = 0), and relative to 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be about 70 parts by weight or more.

[0072] In another embodiment, relative to 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be about 70 parts by weight or more, for example, about 80 parts by weight or more, or about 90 parts by weight or more, or may be about 100 parts by weight or less, for example, about 99 parts by weight or less, or about 95 parts by weight or less.

[0073] In one embodiment of the present application, pure silicon (Si) particles may be used as the silicon-based active material. Using pure silicon (Si) particles as the silicon-based active material may mean that relative to a total of 100 parts by weight of the silicon-based active material as described above, the content of pure Si particles (SiOx (x = 0)) not combined with other particles or elements is within the above range.

[0074] In one embodiment of the present application, the silicon-based active material may be composed of silicon-based particles in which, relative to 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 100 parts by weight.

[0075] In one embodiment of the present application, the silicon-based active material may contain metal impurities. Here, the impurities are metals that can generally be contained in the silicon-based active material, and relative to 100 parts by weight of the silicon-based active material, the content may be, for example, about 0.1 part by weight or less.

[0076] The silicon-based active material used as the negative electrode active material of the lithium secondary battery has a significantly higher capacity than the conventionally used graphite-based active material, and therefore attempts to apply the silicon-based active material are increasing. However, due to the high volume expansion rate during the charge and discharge process, these attempts are limited to the case where a trace amount of the silicon-based active material is mixed with the graphite-based active material and used.

[0077] On the other hand, in the case of the present invention, while using the silicon-based active material as a negative electrode active material to improve capacity performance, conventional problems have been solved by adjusting (controlling) the grain size of the silicon-based active material itself rather than adjusting the composition of the conductive material and the binder.

[0078] In the method for manufacturing the negative electrode active material of the present application, in order to reduce the grain size, before MG-Si is pulverized, a rapid cooling process is performed to prepare a plate-like silicon precursor, and then the silicon-based active material is manufactured by pulverizing the precursor.

[0079] In one embodiment of the present application, the silicon precursor satisfies the following Formulas 3 and 4.

[0080] [Formula 3]

[0081] About 10µm≤Si precursor sheet thickness≤about 2mm

[0082] [Formula 4]

[0083] About 2nm≤Grain size of silicon precursor≤about 1µm

[0084] In one embodiment of the present application, the above Formula 3 satisfies about 10 μm ≤ the plate thickness of the silicon precursor ≤ 2 mm, about 13 μm ≤ the plate thickness of the silicon precursor ≤ 1.5 mm, or about 15 μm ≤ the plate thickness of the silicon precursor ≤ 1 mm.

[0085] In one embodiment of the present application, the above formula 4 satisfies about 2nm≤the grain size of the silicon precursor≤about 1µm, or may satisfy, for example, about 10nm≤the grain size of the silicon precursor≤about 1µm, or about 40nm≤the grain size of the silicon precursor≤about 1µm.

[0086] refer to Figure 1According to one embodiment of the present invention, in the process of forming a plate-like silicon precursor by melt spinning, first, MG silicon is placed in a graphite crucible, and a current of about 10kA is passed through a copper coil to prepare molten silicon at about 2000°C (S1). Next, a plate-like silicon precursor is manufactured by injecting molten silicon into a copper wheel with a diameter of 25cm at a pressure of 1.2kPa and rotating it at a speed of 3000rpm (S2). On the other hand, it is checked whether the prepared precursor satisfies formulas 3 and 4 (S3). Then, when formulas 3 and 4 are satisfied (S3, yes), the prepared silicon precursor is crushed by a method such as ball milling, pin milling, disc milling or jet milling to form a silicon-based active material (S4). When the prepared precursor does not satisfy formulas 3 and 4 in S3, the process returns to step S1 and repeats the step of preparing molten metal silicon, or the process returns to step S2 and repeats the step of preparing plate-like metal silicon by rapidly cooling molten metal silicon. On the other hand, it is checked in step S5 whether the formed active material satisfies formulas 1 and 2. Then, when formula 1 and 2 are satisfied (yes, S5), a silicon-based active material is obtained in step S6, and the process ends. Thereafter, the obtained silicon-based active material can be used to manufacture, for example, a negative electrode of a lithium secondary battery. On the other hand, when the formed active material does not satisfy formula 1 and 2 in step S5 (S5, no), the process returns to step S4 and repeats the steps.

[0087] In the method for manufacturing the negative electrode active material of the present application, in order to reduce the grain size, before the MG-Si is crushed, the molten MG-Si is subjected to a rapid cooling process to prepare a plate-like silicon precursor, and then the prepared silicon precursor is adjusted accordingly to satisfy the above formulas 3 and 4.

[0088] The silicon-based active material having nano-sized crystal grains can be obtained by pulverizing the plate-like silicon precursor having nano-sized crystal grains, which can then be used to manufacture a negative electrode. Therefore, for example, the cycle capacity retention rate and initial capacity efficiency of the secondary battery are improved.

[0089] In one embodiment of the present application, the silicon-based active material may be formed by pulverizing the plate-like silicon precursor, and the silicon-based active material according to the present application satisfies the following Formulas 1 and 2.

[0090] [Formula 1]

[0091] About 1µm≤Particle size of silicon-based active materials (D50)≤10µm

[0092] [Formula 2]

[0093] About 2nm≤Grain size of silicon-based active materials≤1µm

[0094] The above formula 1 may satisfy, for example, a range of about 3 µm ≤ the particle size (D50) of the silicon-based active material ≤ 9 µm or about 3 µm ≤ the particle size (D50) of the silicon-based active material ≤ 7 µm.

[0095] Furthermore, the above Formula 2 may satisfy, for example, about 5 nm ≤ the grain size of the silicon-based active material ≤ 700 nm, or about 20 nm ≤ the grain size of the silicon-based active material ≤ 500 nm.

[0096] As described above, when the silicon precursor is formed, the grain size is adjusted, and a pulverization process is additionally performed, thereby finally satisfying the grain size within the range of the above Formula 2. Therefore, the cycle capacity retention rate and initial capacity efficiency of the secondary battery are improved.

[0097] In one embodiment of the present application, the grain size can be calculated by the full width at half maximum (FWHM) value obtained by XRD analysis. Figure 5 Grain size calculation methods can be found in . Figure 5 In the above, all values ​​except the L value can be measured by XRD analysis of silicon-based active materials, and the grain size can be measured by the Debye-Scherrer formula, where FWHM is inversely proportional to the grain size. Here, the Debye-Scherrer formula is shown in the following formula 1-1.

[0098] [Formula 1-1]

[0099] FWHM=Kλ / LCosθ

[0100] In the above formula 1-1,

[0101] L is the grain size, K is a constant, θ is the Bragg angle, and λ represents the X-ray wavelength.

[0102] Furthermore, the shape of the crystal grains is various and can be measured three-dimensionally, and the size of the crystal grains can be measured by a generally used circle method or diameter measurement method, but the present invention is not limited thereto.

[0103] In the diameter measurement method, the measurement can be performed by drawing 5 to 10 equilibrium lines (the length of one line is L mm) on a micrograph of the target particle, and counting and averaging the number z of crystal grains on these lines. Here, only those crystal grains that are completely present on the line are counted, and those crystal grains that are partially present on the line are excluded. If the number of lines is P and the magnification is V, the average particle diameter can be calculated by the following formula 1-2.

[0104] [Formula 1-2]

[0105] Dm = (L*P*10 3 ) / (zV) (μm)

[0106] In addition, the circle method is a method in which a circle having a predetermined diameter is drawn on a micrograph of a target particle, and the average area of ​​the crystal grains is obtained from the number of crystal grains existing within the circle and the number of crystal grains existing on the boundary line. The calculation can be performed by the following formula 1-3.

[0107] [Formula 1-3]

[0108] Fm = (Fk * 10 6 ) / ((0.67n + z) V 2 ) (μm 2 )

[0109] In the above formula 1-3, Fm represents the average particle area, Fk represents the measurement area on the photograph, z represents the number of particles existing in the circle, n represents the number of particles existing on the arc, and V represents the magnification of the microscope.

[0110] In a negative electrode active material provided in one embodiment of the present application, the silicon-based active material includes silicon-based crystal grains, and a high-angle grain boundary ratio in the silicon-based crystal grains is about 30% or more.

[0111] In another embodiment, the silicon-based active material comprises silicon-based grains, and the high-angle grain boundary ratio in the silicon-based grains may be about 30% or more, 35% or more, or 40% or more, or may be about 80% or less, 75% or less, or 70% or less.

[0112] In the present application, the silicon-based grains may refer to individual particles forming the silicon-based active material, and the silicon-based grains may be collected to form the silicon-based active material. Here, grain boundaries may be defined as defects between corresponding grains.

[0113] When the manufacturing method is used, many high-angle grain boundaries (HAGB) having high grain boundary energy are formed. In the case of the high-angle grain boundaries, diffusion of lithium ions is easier than in the low-angle grain boundaries (LAGB).

[0114] In the present application, the high-angle grain boundary ratio may refer to a ratio of grain boundaries having an orientation misorientation angle of about 15° or more in the entire silicon-based active material.

[0115] In the present application, the high-angle grain boundary may mean that the misorientation angle is greater than about 15°, and the low-angle grain boundary may mean that the misorientation angle is about 2°<(misorientation angle)<15°.

[0116] Figure 64 is a view showing the misorientation angle. The corresponding misorientation angle 4 can be defined as the angle of the crystal orientation difference between two adjacent silicon-based crystal grains 2. Here, the grain boundary can be defined as a crystal defect between different silicon-based crystal grains 2.

[0117] In the silicon-based active material according to the present application, high-angle grain boundaries may be formed at a relatively high ratio relative to all grain boundaries, thereby improving battery performance.

[0118] In the negative electrode active material provided in one embodiment of the present application, the average misorientation angle of the silicon-based crystal grains is about 5° or more.

[0119] Figure 2 An enlarged view of a silicon-based active material according to one embodiment of the present application is shown. For example, the silicon-based active material 1 is composed of a plurality of silicon-based crystal grains 2, and here, the crystal grains have a grain size of the above formula 2. In addition, crystal defects between the silicon-based crystal grains can be defined as grain boundaries.

[0120] In one embodiment of the present application, the silicon-based active material may include silicon-based particles having a particle size distribution of about 0.01 μm to 30 μm.

[0121] The fact that the silicon-based active material contains silicon-based particles having a particle size distribution of about 0.01 μm to 30 μm means that a large number of individual silicon-based particles having a particle size falling within the above range are contained. The number of silicon-based particles contained is not limited.

[0122] When the silicon-based particles are spherical, the particle size can be represented by the diameter of the particles, and even if the silicon-based particles have a shape different from a sphere, the particle size as compared with the case of a sphere can be measured. Generally, the particle size of a single silicon-based particle can be measured by a method for measurement in the art.

[0123] In one embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and may be, for example, not porous. The silicon particles may be, for example, spherical or fragmentary particles. According to one embodiment, the silicon particles may also have a fibrous structure, or may be present in the form of a silicon-containing film or coating.

[0124] In one embodiment of the present application, a negative electrode composition is provided, the negative electrode composition comprising the negative electrode active material; a negative electrode conductive material; and a negative electrode binder.

[0125] In the negative electrode composition provided in one embodiment of the present application, the negative electrode active material accounts for about 40 parts by weight or more relative to 100 parts by weight of the negative electrode composition.

[0126] In another embodiment, the content of the negative electrode active material may be about 40 parts by weight or more, or may be, for example, 60 parts by weight or more, 65 parts by weight or more, or 70 parts by weight or more, relative to 100 parts by weight of the negative electrode composition, and may be 95 parts by weight or less, 90 parts by weight or less, or 85 parts by weight or less.

[0127] The negative electrode composition according to the present application uses a negative electrode active material that satisfies the specific surface area size, so that even when a silicon-based active material with a significantly high capacity within the above range is used, the volume expansion rate during the charge and discharge process can be controlled. Therefore, it is characterized in that even if the content of the silicon-based active material falls within the above range, the performance of the negative electrode will not deteriorate, and the output characteristics in charge and discharge are improved relative to conventional secondary batteries.

[0128] Conventionally, graphite compounds are generally used as negative electrode active materials. On the other hand, recently, as the demand for high-capacity batteries increases, more and more attempts are being made to increase capacity by mixing and using the silicon-based active materials. However, as described above, even if the properties of the silicon-based active material itself are adjusted, the volume of the silicon-based active material rapidly expands during the charge and discharge process, which may cause a problem of destroying the conductive path formed in the negative electrode active material layer.

[0129] In one embodiment of the present application, the negative electrode conductive material may include at least one selected from the group consisting of point-shaped conductive materials, planar conductive materials, and linear conductive materials.

[0130] In one embodiment of the present application, the dot-shaped conductive material refers to a dot-shaped or spherical conductive material, which can be used to improve the conductivity of the negative electrode and has conductivity without causing chemical changes. For example, the dot-shaped conductive material can be at least one type selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and in one embodiment, carbon black can be included in terms of the realization of high conductivity and improved dispersibility.

[0131] In one embodiment of the present application, the BET specific surface area of ​​the dot-shaped conductive material may be about 40 m 2 / g to 70m 2 / g, or it may be, for example, 45m 2 / g to 65m 2 / g, or 50m 2 / g to 60m 2 / g.

[0132] In one embodiment of the present application, the functional group content (volatile matter) of the dot-shaped conductive material may satisfy a range of about 0.01% to about 1%, for example, about 0.01% to about 0.3%, or about 0.01% to about 0.1%.

[0133] When the functional group content of the dot-shaped conductive material satisfies the above range, since the functional groups are present on the surface of the dot-shaped conductive material, when water is used as a solvent, the dot-shaped conductive material can also be smoothly dispersed in the solvent. For example, in the present invention, by using a specific silicon-based active material, the functional group content of the dot-shaped conductive material can be reduced. This leads to an improved effect of improved dispersibility.

[0134] In one embodiment of the present application, in addition to the silicon-based active material, the dot-shaped conductive material having a functional group content falling within the above range is further included. The functional group content can be adjusted according to the degree of heat treatment of the dot-shaped conductive material.

[0135] In one embodiment of the present application, the particle size of the dot-shaped conductive material may be about 10 nm to about 100 nm, or may be, for example, about 20 nm to 90 nm, or about 20 nm to 60 nm.

[0136] In one embodiment of the present application, the conductive material may include a planar conductive material.

[0137] The planar conductive material can improve the conductivity by increasing the surface contact between silicon particles in the negative electrode, and at the same time, inhibit the disconnection of the conductive path due to volume expansion. The planar conductive material can be described as a plate-shaped conductive material or a block-shaped conductive material.

[0138] In one embodiment of the present application, the planar conductive material may include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and according to one embodiment, may be plate-like graphite.

[0139] In one embodiment of the present application, the average particle size (D50) of the planar conductive material may be about 2 μm to 7 μm, and may be, for example, about 3 μm to 6 μm, or about 3.5 μm to 5 μm. When the above range is met, the dispersion is easy due to the sufficient particle size without causing excessive increase in the viscosity of the negative electrode slurry. Therefore, in the dispersion using the same equipment and time, the dispersion effect is improved.

[0140] In the negative electrode composition provided in one embodiment of the present application, D10 of the planar conductive material may be about 0.5 μm to 2.0 μm, D50 may be about 2.5 μm to 3.5 μm, and D90 may be about 6.5 μm to 15.0 μm.

[0141] In one embodiment of the present application, as the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area or a low specific surface area planar conductive material can be used.

[0142] In one embodiment of the present application, although the high specific surface area-planar conductive material or the low specific surface area-planar conductive material can be used as the planar conductive material without restriction, since according to one embodiment, the electrode performance may be affected to a certain extent by the dispersion of the planar conductive material, a low specific surface area-planar conductive material that does not cause dispersion problems can be used.

[0143] In one embodiment of the present application, the BET specific surface area of ​​the planar conductive material may be about 0.25 m 2 / g or above.

[0144] In another embodiment, the BET specific surface area of ​​the planar conductive material may be about 1 mm 2 / g to 500m 2 / g, and may be, for example, about 5 m 2 / g to 300m 2 / g, or 5m 2 / g to 250m 2 / g.

[0145] As the planar conductive material according to the present application, a high specific surface area-planar conductive material or a low specific surface area-planar conductive material can be used.

[0146] In another embodiment, the planar conductive material is a high specific surface area planar conductive material, and its BET specific surface area can meet about 50m 2 / g to 500m 2 / g, for example, about 80m 2 / g to 300m 2 / g, or 100m 2 / g to 300m 2 / g range.

[0147] In another embodiment, the planar conductive material is a low specific surface area-planar conductive material, and its BET specific surface area can meet about 1m 2 / g to 40m 2 / g, for example, about 5m 2 / g to 30m 2 / g, or 5m 2 / g to 25m 2 / g range.

[0148] Other conductive materials may include linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. For example, herein, unless otherwise specified, "bundle-type" refers to a secondary shape in the form of a bundle or rope, in which carbon nanotube units are arranged side by side or entangled, and the longitudinal axes of the carbon nanotube units are substantially in the same orientation. The carbon nanotube units have a graphite surface (graphite sheet) in the form of a cylinder with a nanometer-sized diameter, and have an sp2 bonding structure. Here, according to the angle and structure in which the graphite surface is rolled, the characteristics of a conductor or a semiconductor may be exhibited. Compared with entangled carbon nanotubes, during the manufacture of the negative electrode, the bundle-type carbon nanotubes may be uniformly dispersed, and then a conductive network may be smoothly formed in the negative electrode, thereby improving the conductivity of the negative electrode.

[0149] In the negative electrode composition provided in one embodiment of the present application, the negative electrode conductive material accounts for about 10 parts by weight to 40 parts by weight relative to 100 parts by weight of the negative electrode composition.

[0150] In another embodiment, the negative electrode conductive material may be contained in an amount of about 0.1 to 40 parts by weight, for example, about 0.2 to 30 parts by weight, about 0.4 to 25 parts by weight, or about 0.4 to 10 parts by weight, relative to 100 parts by weight of the negative electrode composition.

[0151] In the negative electrode composition provided in one embodiment of the present application, the negative electrode conductive material includes a planar conductive material; and a linear conductive material.

[0152] In the negative electrode composition provided in one embodiment of the present application, in the negative electrode conductive material, the content of the planar conductive material may be about 80 parts by weight to 99.9 parts by weight relative to 100 parts by weight of the negative electrode conductive material; and the content of the linear conductive material may be about 0.1 parts by weight to 20 parts by weight.

[0153] In another embodiment, in the negative electrode conductive material, the content of the planar conductive material may be about 80 parts by weight to 99.9 parts by weight, for example, about 85 parts by weight to 99.9 parts by weight, or 95 parts by weight to 98 parts by weight, relative to 100 parts by weight of the negative electrode conductive material.

[0154] In another embodiment, in the negative electrode conductive material, the content of the linear conductive material may be about 0.1 to 20 parts by weight, for example, 0.1 to 15 parts by weight, or 0.2 to 5 parts by weight, relative to 100 parts by weight of the negative electrode conductive material.

[0155] In one embodiment of the present application, when the negative electrode conductive material includes the planar conductive material and the linear conductive material, and these conductive materials satisfy the above composition and ratio, the existing life characteristics of the lithium secondary battery are not significantly affected. For example, when the planar conductive material and the linear conductive material are included, the chargeable and dischargeable points increase. Therefore, relative to conventional secondary batteries, at high C rates, the output characteristics of the secondary battery are improved and the amount of high temperature gas generated is reduced.

[0156] In one embodiment of the present application, the negative electrode conductive material may be composed of the planar conductive material. When the linear conductive material is used alone, the problems of the silicon-based negative electrode, such as electrode distortion, can be simplified, and the electrode structure can be improved. Therefore, the movement resistance of lithium ions in the electrode can be reduced.

[0157] In one embodiment of the present application, when the negative electrode conductive material contains only the linear conductive material, the content of the negative electrode conductive material may be about 0.1 to 5 parts by weight, for example, about 0.2 to 3 parts by weight, or about 0.4 to 1 part by weight, relative to 100 parts by weight of the negative electrode composition.

[0158] The negative electrode conductive material according to the present application has a structure that is basically independent of the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application plays a role in controlling the contact points between the silicon-based active materials that cause a very large expansion of the electrode volume during charging and discharging. On the other hand, the positive electrode conductive material plays a buffering role during rolling and plays a role in providing a certain conductivity, and therefore has a structure and function that are basically different from the negative electrode conductive material of the present invention.

[0159] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material, and it has a substantially different configuration from the conductive material applied to the graphite-based active material. For example, the conductive material used for the electrode with the graphite-based active material has only particles smaller than the active material, and has the characteristics of improving output characteristics and providing a certain conductivity, and thus has a substantially different configuration and function from the negative electrode conductive material applied together with the silicon-based active material as in the present invention.

[0160] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and function different from the carbon-based active material commonly used as the negative electrode active material. For example, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed and used in a spherical or dot shape to facilitate the storage and release of lithium ions.

[0161] On the other hand, the planar conductive material used as the negative electrode conductive material is a material having a plane or plate shape, and can be expressed as plate-like graphite. For example, the planar conductive material is a material included to maintain a conductive path within the negative electrode active material layer, and refers to a material that is not used as a role of storing and releasing lithium, but is used to ensure a conductive path through the surface shape within the negative electrode active material layer.

[0162] That is, in the present application, the fact that the plate-like graphite is used as a conductive material means that the graphite is processed into a planar or plate-like shape and is not used as a role of storing and releasing lithium, but is used as a material for ensuring a conductive path. Here, the negative electrode active material included with the planar graphite has a high capacity characteristic in terms of storing and releasing lithium, and plays a role of storing and releasing all lithium ions transferred from the positive electrode.

[0163] On the other hand, in the present application, using the carbon-based active material as an active material means that the carbon-based active material is processed into a dot shape or a spherical shape and used as a material that plays a role in storing or releasing lithium.

[0164] For example, in one embodiment of the present application, artificial graphite or natural graphite as a carbon-based active material may have a dot shape, and its BET specific surface area may satisfy 0.1 m 2 / g and 4.5m 2 In addition, the planar graphite as the planar conductive material may have a planar shape, and its BET specific surface area may be about 5 m 2 / g or above.

[0165] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and their substitutes obtained by replacing hydrogen with Li, Na or Ca, and may also include various copolymers of these materials.

[0166] The negative electrode binder according to one embodiment of the present application plays a role in retaining the active material and the conductive material to prevent the distortion and structural deformation of the negative electrode structure during the volume expansion and relaxation of the silicon-based active material. Any general binder can be applied as long as the above-mentioned role is met. For example, an aqueous binder can be used or a PAM-based binder can be used.

[0167] In one embodiment of the present application, the negative electrode binder may account for about 30 parts by weight or less, for example, or may account for about 25 parts by weight or less or about 20 parts by weight or less, and about 5 parts by weight or more or about 10 parts by weight or more, relative to 100 parts by weight of the negative electrode composition.

[0168] According to one embodiment of the present application, a method for manufacturing a negative electrode active material is provided. The method for manufacturing the negative electrode active material comprises: a step of rapidly cooling metallic silicon to form a silicon precursor; and a step of crushing the silicon precursor to form a silicon-based active material. The rapid cooling step comprises melt spinning, suction casting or injection casting.

[0169] As described above, in the production of the silicon-based active material, the metal silicon itself is not directly pulverized, but the grain size of the silicon precursor formed by adjusting the cooling rate in the rapid cooling process is adjusted and the precursor is pulverized.

[0170] That is, the shorter the solidification time (Ts) during casting of molten silicon, the faster the cooling rate. Since the plate thickness of the silicon precursor satisfies the range of the above formula 3 (e.g., about 10 μm to 2 mm), the solidification time is short, and thus the cooling rate can be increased by adjustment. In addition, as described above, since the cooling rate is increased by adjustment, the grain growth time is short, and the above-mentioned grain size (e.g., about 2 nm to 11 μm) can be met.

[0171] The method for manufacturing a negative electrode active material provided in one embodiment of the present application further includes a step of heating the metal silicon in an induction furnace before the step of forming a silicon precursor by rapidly cooling the metal silicon.

[0172] As described above, when the metallic silicon is in a molten state by heating in an induction furnace and then undergoes a rapid cooling step, the rapid cooling includes melt spinning, suction casting or injection casting. According to the purpose of the present invention, any method capable of forming a plate-like silicon precursor by rapidly cooling molten metallic silicon can be used.

[0173] Generally, melt spinning refers to a process in which a molten material is injected into a rotating Cu wheel and rapidly cooled. In addition, suction casting refers to a casting process in which the molten material is sucked from below the mold in a vacuum, and injection casting refers to a casting process in which the molten material is introduced into the mold by high-pressure gas.

[0174] In the case of the above-mentioned rapid cooling step, since the melt spinning, suction casting and injection casting processes are different and diverse from each other, it is difficult to roughly specify the conditions, but as a result, a plate-shaped silicon precursor can be manufactured in all cases.

[0175] In the present application, during the rapid cooling, cooling rate regulation is difficult for each process, but, generally, in melt spinning, the faster the rotation speed of the wheel, the faster the cooling rate, and in the case of suction casting or injection casting, the thinner the mold thickness, the faster the cooling rate. In addition, the cooling rate can be controlled by controlling the external temperature through a method such as causing cooling water to flow into the mold or by cooling the wheel or mold by liquid nitrogen or the like. On the other hand, rapid cooling is a cooling method for forming a plate-like metallic silicon precursor by rapidly cooling molten MG silicon. The rapid cooling is a solidification process performed in a non-equilibrium state, in which reactions such as phase change or grain coarsening that occur in cooling in an equilibrium state are suppressed. For example, when MG silicon is rapidly cooled using melt spinning, the cooling temperature can be controlled by adjusting the rotation speed of the Cu wheel, and it takes about less than one second for molten MG silicon of about 1,500°C to cool to an ambient temperature of about 25°C.

[0176] In the negative electrode active material manufacturing method provided in one embodiment of the present application, after the step of forming the silicon precursor by rapidly cooling the metal silicon, the silicon precursor satisfies Formulas 3 and 4 above.

[0177] The silicon precursor formed by the rapid cooling process satisfies Formulas 3 and 4.

[0178] In the method for producing a negative electrode active material provided in the present application, after the step of forming the silicon-based active material by pulverizing the silicon precursor, the silicon-based active material satisfies Formulas 1 and 2 above.

[0179] After the silicon precursor satisfying specific formulas 3 and 4 is formed through the rapid cooling process, a silicon-based active material satisfying the range of the above formulas 1 and 2 may be manufactured through a pulverization process of the silicon precursor.

[0180] In one embodiment of the present application, the pulverization process may include one or more processes selected from the group consisting of ball milling, pin milling, disc milling and jet milling, but is not limited thereto. Any process may be applied as long as it is a pulverization process by which the plate-like metallic silicon precursor is pulverized to produce a silicon-based active material satisfying the range of the above formulas 1 and 2.

[0181] Through the above-mentioned pulverization process, a silicon-based active material satisfying the above-mentioned ranges of Formulas 1 and 2 can be produced.

[0182] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided. The negative electrode comprises a negative electrode collector layer; and a negative electrode active material layer formed on one surface or both surfaces of the negative electrode collector layer. The negative electrode active material layer comprises the negative electrode composition according to the present application or a cured product thereof.

[0183] Figure 31 is a view showing a stacked structure of a negative electrode for a lithium secondary battery according to one embodiment of the present application. For example, it can be seen that the negative electrode 100 for a lithium secondary battery includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10 . Figure 3 The negative electrode active material layer is shown to be formed on one surface of the negative electrode collector layer, but the negative electrode active material layer may be included on both surfaces of the negative electrode collector layer.

[0184] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by coating a negative electrode slurry containing the negative electrode composition on one surface or both surfaces of the negative electrode collector layer and drying the coating.

[0185] Here, the negative electrode slurry may include the negative electrode composition described above; and a slurry solvent.

[0186] In one embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of about 5% to 40%.

[0187] In another embodiment, the solid content of the negative electrode slurry may satisfy a range of about 5% to 40%, such as about 7% to 35%, or about 10% to 30%.

[0188] The solid content of the negative electrode slurry may mean the content of the negative electrode composition included in the negative electrode slurry, and may mean the content of the negative electrode composition relative to 100 parts by weight of the negative electrode slurry.

[0189] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate in the formation of the negative electrode active material layer. Therefore, the particle agglomeration of the negative electrode composition can be minimized, and thus, the negative electrode active material layer can be effectively formed.

[0190] In one embodiment of the present application, the slurry solvent may be used without limitation as long as the slurry solvent can dissolve the negative electrode composition. For example, water or N-methyl-2-pyrrolidone (NMP) may be used.

[0191] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of about 1 μm to 100 μm. This negative electrode current collector layer is not particularly limited, as long as the negative electrode current collector layer has high conductivity and does not cause chemical changes in the corresponding battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloys can be used. In addition, the adhesion to the negative electrode active material can be enhanced by forming fine concave-convex on the surface, and can be used in various forms such as films, sheets, foils, nets, porous bodies, foams and non-woven fabrics.

[0192] In the negative electrode for a lithium secondary battery provided in one embodiment of the present application, the thickness of the negative electrode collector layer is about 1 μm to 100 μm, and the thickness of the negative electrode active material layer is about 5 μm to 500 μm.

[0193] However, the thickness may be variously modified depending on the type and application of the negative electrode to be used.

[0194] In one embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of about 10% to 60%.

[0195] In another embodiment, the porosity of the negative electrode active material layer may satisfy a range of about 10% to 60%, for example, about 20% to 50%, or about 30% to 45%.

[0196] The porosity varies according to the composition and content of the silicon-based active material, the conductive material, and the binder contained in the negative electrode active material layer. For example, when the composition and content of the silicon-based active material and the conductive material contained according to the present application become specific values, the above range is satisfied. Therefore, in the electrode, the conductivity and resistance satisfy the appropriate range.

[0197] In one embodiment of the present application, a lithium secondary battery is provided, which includes a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0198] Figure 4 1 is a view showing a stacked structure of a lithium secondary battery according to an embodiment of the present application. For example, a negative electrode 100 for a lithium secondary battery can be seen, which includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10. A positive electrode 200 for a lithium secondary battery can be seen, which includes a positive electrode active material layer 40 on one surface of a positive electrode collector layer 50. It can be seen that the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are formed in a stacked structure together with a separator 30 interposed therebetween.

[0199] A secondary battery according to an embodiment of the present specification may include the above-mentioned negative electrode for a lithium secondary battery. For example, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description will be omitted.

[0200] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0201] In the positive electrode, the positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can generally have a thickness of 3μm to 500μm, and fine concavoconvexities can also be formed on the surface of the current collector to increase the adhesion to the positive electrode active material. For example, it can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0202] The positive electrode active material may be a commonly used positive electrode active material. For example, examples of the positive electrode active material may include: a layered compound such as lithium cobalt oxide (LiCoO 2 ) and lithium nickel oxide (LiNiO 2 ) or compounds substituted by one or more transition metals; lithium iron oxides, such as LiFe 3 O 4 ; Lithium manganese oxide, such as Li 1+c1 Mn 2-c1 O 4 (0≤c1≤0.33), LiMnO 3 、LiMn 2 O 3 and LiMnO 2 ; Lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 、V 2 O 5 and Cu 2 V 2 O 7 ; Ni-site lithium nickel oxide, with the chemical formula LiNi 1-c2 M c2 O 2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); a lithium manganese composite oxide having a chemical formula of LiMn 2-c3 M c3 O 2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li 2 Mn 3 MO 8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); and LiMn 2 O4 , wherein a portion of Li in the chemical formula is replaced by alkaline earth metal ions, but is not limited to these. The positive electrode can also be Li-metal.

[0203] In addition to the positive electrode active material, the positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder.

[0204] The positive electrode conductive material is used to impart conductivity to the electrode, and can be used in the constituted battery without particular limitation, as long as it has electronic conductivity without causing chemical changes. Examples may include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., one of which may be used alone or a mixture of two or more may be used.

[0205] In addition, the positive electrode binder plays a role in improving the adhesion between the particles of the positive electrode active material and the adhesion strength between the positive electrode active material and the positive electrode current collector. Examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one may be used alone or a mixture of two or more may be used.

[0206] The separator separates the negative electrode and the positive electrode from each other and provides a path for the movement of lithium ions, and can be used without particular limitation, as long as the separator is generally used as a separator in a secondary battery. An example is a separator having low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention. For example, a porous polymer film or a stacked structure of two or more layers of these can be used. For example, the porous polymer film can be made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers. In addition, conventional porous non-woven fabrics can also be used, such as non-woven fabrics made of high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated separator containing a ceramic component or a polymer material can also be used to ensure heat resistance or mechanical strength, and can be optionally used in a single-layer or multilayer structure.

[0207] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, and a molten inorganic electrolyte that may be used to manufacture a lithium secondary battery, but are not limited thereto.

[0208] For example, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0209] As the non-aqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.

[0210] Among the above carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, can be used because they are high-viscosity organic solvents and can easily dissociate lithium salts due to their high dielectric constants. Also, when mixed with linear carbonates having low viscosity and low dielectric constants such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte having high conductivity can be prepared, so such a combined use may be more preferred.

[0211] As the metal salt, a lithium salt may be used, and the lithium salt is a material that can be easily dissolved in the non-aqueous electrolyte. For example, as the anion of the lithium salt, one or more selected from the group consisting of: F - , Cl - ,I - 、NO 3 - 、N(CN) 2 - , BF 4 - , ClO 4 - PF 6 - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、CF 3 SO 3 - 、CF 3 CF 2 SO 3 - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、CF 3 CF 2 (CF 3 ) 2 CO - 、(CF 3 SO 2 ) 2 CH - 、(SF 5 ) 3 C - 、(CF 3 SO 2 ) 3 C - 、CF 3 (CF 2 ) 7 SO 3 - 、CF 3 CO 2 - 、CH 3 CO 2 - 、SCN - 和(CF 3 CF 2 SO 2 ) 2 N - 。

[0212] For the purpose of improving battery life characteristics, inhibiting battery capacity reduction and improving battery discharge capacity, in addition to the electrolyte components, the electrolyte may also contain one or more additives, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0213] In one embodiment of the present invention, a battery module including the above-mentioned secondary battery as a unit cell and a battery pack including the battery module are provided. The battery module and the battery pack include the above-mentioned secondary battery having high capacity and high rate characteristics and cycle characteristics, and can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0214] Example

[0215] Hereinafter, embodiments are provided to facilitate understanding of the present invention. However, the following embodiments are merely illustrative of the present description, and it is obvious to those skilled in the art that various changes and modifications may be made within the scope of the present description and the scope of the technical concept, and naturally, these changes and modifications fall within the scope of the attached patent claims.

[0216] <Production Example>

[0217] <Manufacturing of Silicon Precursor>

[0218] <Example 1>

[0219] The MG silicon is placed in a graphite crucible and melted by using an induction furnace, and then formed into a plate-shaped silicon precursor through a melt-spinning process.

[0220] For example, a current of 10 kA is passed through a copper coil to prepare molten silicon at 2000° C., and then the molten silicon is injected into a copper wheel having a rotation speed of 3000 rpm and a diameter of 25 cm at a pressure of 1.2 kPa to obtain a plate-shaped silicon precursor. Here, it can be found that the plate thickness of the silicon precursor is about 20 μm, and the grain size is about 50 nm, which respectively satisfy the above-mentioned equations 3 and 4.

[0221] In Examples 2 and 3 and Comparative Example 3, a silicon precursor was prepared in the same manner as in Example 1, except that the rotation speed of Example 1 was changed to the conditions in Table 1 below to control the cooling rate during rapid cooling using melt spinning.

[0222]

[0223] In the case of Example 2, the rotation speed of the copper wheel in the melt spinning process is 4000 rpm, which is higher than 3000 rpm in Example 1. In this case, it can be found that the plate thickness of the silicon precursor is about 15 μm, and the grain size is about 40 nm, which respectively satisfy the above formulas 3 and 4. In addition, in the case of Example 3, the rotation speed of the copper wheel in the melt spinning process is 1000 rpm. Also in this case, it can be found that the plate thickness of the silicon precursor is about 100 μm, and the grain size is about 300 nm, which respectively satisfy the above formulas 3 and 4.

[0224] In the case of Comparative Examples 1 and 2, instead of being placed in a graphite crucible, melted using an induction furnace, and formed into a plate-like silicon precursor through a melt spinning process, the MG silicon itself was used as it is to perform the pulverization process described below. On the other hand, in the case of Comparative Example 3, the rotation speed of the copper wheel in the melt spinning process was 100 rpm. The plate thickness of the silicon precursor was about 3 mm, which was thicker than those in the examples of the present invention, and the grain size was 2.5 μm, which was larger than those in the examples of the present invention, so it can be found that the above-mentioned formulas 3 and 4 are not satisfied.

[0225] <Example 4>

[0226] In Example 4, unlike the above-mentioned Examples 1, 2 and 3, the MG silicon is placed in a molten state by arc melting and then a plate-shaped silicon precursor is formed by a suction casting process.

[0227] For example, set the vacuum level to 10 -6 The interior of the chamber of the holder is filled with argon gas at a pressure of 0.5 kPa to form a high-purity argon atmosphere. Then, molten silicon at 2000°C is prepared by using arc plasma. Next, the vacuum degree at the bottom of the mold is maintained at 10 -5 After the support is above, the valve between the bottom of the mold and the chamber is opened. Then, the molten silicon is sucked into the mold to prepare a plate-shaped silicon precursor. The size of the mold used in this article is 0.5mm thick, 10mm wide, 50mm long, and the grain size is 50nm.

[0228] A silicon precursor was prepared in the same manner as in Example 4, except that the mold thickness (cooling rate determined during rapid cooling using suction casting) in Example 4 was changed to the conditions of Table 2 below.

[0229]

[0230] It can be found that in the case of Examples 4, 5 and 6, the plate thickness of the silicon precursor is 500 μm, 400 μm and 100 μm, respectively, which satisfies the condition of Formula 3, and the grain size of the silicon precursor is 400 nm, 500 nm and 1,000 nm, respectively, which satisfies Formula 4.

[0231] In the case of Comparative Examples 4 and 5, instead of being in a molten state by arc melting and then formed into a plate-like silicon precursor by a suction casting process, the MG silicon itself was used as it was to perform the pulverization process described below.

[0232] On the other hand, it can be found that in the case of Comparative Example 6 where the plate-shaped mold thickness is 3 mm, the plate thickness of the silicon precursor is 3 mm, which does not satisfy the condition of Formula 3, and the grain size of the silicon precursor is 2.510 μm, which does not satisfy Formula 4.

[0233] Based on the values ​​of Tables 1 and 2 above, it was confirmed that it is generally easier to prepare a thinner silicon precursor in the melt spinning process than in the suction casting process.

[0234] <Manufacturing of Silicon-Based Active Materials>

[0235] The silicon precursor prepared above was ball-milled to prepare a silicon-based active material.

[0236] For example, a wet pulverization method is used in which n-hexane is used as a medium, and for the balls, zirconium oxide (ZrO 2 ). Here, the mass ratio of the silicon precursor to the ball was set to about 1:40, and the pulverization was performed for 30 minutes. The particle size of the prepared negative electrode active material was 5 μm, and the grain size was 50 nm, which satisfied Formulas 1 and 2, respectively.

[0237] The silicon precursors of the above Examples and Comparative Examples were pulverized in the same manner as described above, and the results are recorded in Table 3.

[0238]

[0239] From Table 3, it can be found that in all Examples 1 to 6, the particle size (D50) of the silicon-based active material satisfies Formula 1, while in Comparative Examples 5 and 6, the particle size (D50) does not satisfy Formula 1. In addition, it can be found that in all Examples 1 to 6, the grain size of the silicon-based active material satisfies Formula 2, while in all Comparative Examples 1 to 6, the grain size does not satisfy Formula 2. In addition, it can be found that in all Examples 1 to 6, the high-angle grain boundary ratio is 30% or more, but in the case of Comparative Examples 4 to 6, the high-angle grain boundary ratio is less than 30%.

[0240] <Manufacturing of negative electrode>

[0241] According to one embodiment, a negative electrode active material including a silicon-based active material of Table 3, a first conductive material, a second conductive material, and polyacrylamide as a binder are added to distilled water as a solvent for forming a negative electrode slurry in a weight ratio of 80:9.6:0.4:10 to prepare a negative electrode slurry (solid concentration: 25 wt %).

[0242] For example, the first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): about 3.5 μm), and the second conductive material is SWCNT.

[0243] The mixing method involves dispersing the first conductive material, the second conductive material, the binder and water by using a homomixer at about 2500 rpm for 30 minutes. Next, the silicon-based active material is added and dispersed at about 2500 rpm for 30 minutes to prepare the negative electrode slurry.

[0244] The negative electrode slurry was prepared at a temperature of about 85 mg / 25 cm 2 The amount of the negative electrode was coated on both surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector layer, rolled, and dried in a vacuum oven at 130° C. for 10 hours. Then, a negative electrode active material layer (thickness: 33 μm) was formed. It was used as a negative electrode (thickness of the negative electrode: 41 μm, porosity of the negative electrode: 40.0%).

[0245] <Manufacturing of Secondary Battery>

[0246] According to one embodiment, LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O 2 (average particle size (D50): 15µm), carbon black as a conductive material (product name: Super C65, manufacturer: Timcal) and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of about 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration: about 78% by weight).

[0247] The positive electrode slurry was prepared at a temperature of about 537 mg / 25 cm 2 The amount of the positive electrode was coated on both surfaces of an aluminum current collector (thickness: 12 μm) as a positive electrode current collector, rolled, and dried in a vacuum oven at 130° C. for 10 hours. Then, a positive electrode active material layer (thickness: 65 μm) was formed, and a positive electrode (thickness of the positive electrode: about 77 μm, porosity: about 26%) was prepared.

[0248] A lithium secondary battery was manufactured by interposing a polyethylene separator between the positive electrode and the negative electrode of the above-described Examples and Comparative Examples and injecting an electrolyte.

[0249] The electrolyte is prepared by adding about 3 wt % of vinylene carbonate to an organic solvent relative to the total weight of the electrolyte, and adding LiPF4 as a lithium salt at a concentration of about 1 M. 6 In the organic solvent, fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) are mixed in a volume ratio of 10:90.

[0250] <Experimental example>

[0251] Experimental Example 1: Single Battery Life Performance Results

[0252] For the secondary battery comprising the negative electrode manufactured in the embodiment and the comparative example, life evaluation was performed by using an electrochemical charger / discharger and the capacity retention rate was evaluated. The secondary battery was subjected to an in-situ cycle test at 4.2-3.0V and 1C / 0.5C, and in the test, the capacity retention rate was measured by charging / discharging (4.2-3.0V) at 0.33C / 0.33C every 50 cycles.

[0253] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)} x 100

[0254]

[0255] As can be seen in Table 4, when the capacity retention rate is checked according to the cycles in Examples 1 to 6 and Comparative Examples 1 to 6 to which the present invention is applied, it can be found that the capacity retention rate of the comparative example to which the present invention is not applied is lower than that of the embodiment. This corresponds to the result obtained when the grain size of the silicon-based active material satisfies the range according to the present invention. Here, a uniform reaction can be caused in the insertion / extraction reaction of lithium during charge / discharge, and the stress applied to the silicon-based active material can be reduced, thereby alleviating the crushing of the particles, and thus the capacity retention rate of the electrode can be improved.

[0256] Experimental Example 2: Single Cell Resistance Change

[0257] In Experimental Example 1, in the test, after measuring the capacity retention rate by charging / discharging (4.2-3.0 V) at 0.33C / 0.33C every 50 cycles, the resistance was measured by pulse discharging at 2.5C at SOC 50. Then, the resistance increase rate was compared and analyzed.

[0258] For each measurement evaluation of the resistance increase rate, the data of the 200th cycle were calculated, and the results are recorded in Table 5 below.

[0259]

[0260] It can be found from Tables 4 and 5 that in the battery using the silicon prepared in Examples 1 to 6 as the negative electrode active material, the life characteristics and resistance change are excellent. In the case of the negative electrode active material according to one embodiment of the present invention, unlike the conventional pulverization processing method, before the MG-Si is pulverized, a rapid cooling process is performed to form a plate-like silicon precursor, and the grain size is optimized by adjusting the cooling rate. As in the embodiment, by pulverizing a plate-like silicon precursor having nano-sized grains, a silicon-based active material having nano-sized grains and satisfying a specific high-angle grain boundary ratio can be obtained. It can be found that when this silicon-based active material is used to manufacture a negative electrode, the cycle capacity retention rate and the initial capacity efficiency are improved.

[0261] For reference, in the case of Comparative Examples 1 to 3, the particle size (Formula 1) and the grain size (Formula 2) of the silicon-based active material are the same, that is, they are made into a single crystal form. This situation corresponds to the situation where there is no grain boundary inside the particles of the silicon-based active material. Therefore, high-angle grain boundaries cannot exist. The cases of Comparative Examples 4 to 6 correspond to the following situation, in which, since the value of Formula 1 is greater than the value of Formula 2, there are grain boundaries inside the particles, but the high-angle grain boundary ratio does not fall within the scope of the present application. In the case of Examples 1 to 6 of the present application, the manufacture performed by the above-mentioned manufacturing method forms a high-angle grain boundary (HAGB) with a high grain boundary energy at a ratio of Table 3. It can be found that in the case of high-angle grain boundaries, the diffusion of lithium ions is easier than in low-angle grain boundaries (LAGB), so the life characteristics and resistance increase rate are better than those of the comparative example.

[0262] Although the present invention has been described above with reference to the embodiments, a person skilled in the art or a person of ordinary skill in the relevant art will understand that various modifications and changes may be made to the present invention without departing from the spirit and technical field of the present invention described in the patent claims to be described later. Therefore, the technical scope of the present invention is not limited to the contents described in the detailed description of this specification, but should be determined by the patent claims.

Claims

1. A negative electrode active material, the negative electrode active material comprising: A silicon-based active material containing silicon-based grains, wherein the ratio of high-angle grain boundaries in the silicon-based grains is 30% or more, and the silicon-based active material contains a composition satisfying the following formulas 1 and 2: [Formula 1] 1 µm ≤ particle size (D50) of the silicon-based active material ≤ 10 µm [Formula 2] 2 nm ≤ grain size of the silicon-based active material ≤ 1 µm.

2. The negative electrode active material according to claim 1, wherein the silicon-based active material further contains a pulverized product of a silicon precursor, and the silicon precursor contains a composition satisfying the following formulas 3 and 4: [Formula 3] 10 µm ≤ plate thickness of the silicon precursor ≤ 2 mm [Formula 4] 2 nm ≤ grain size of the silicon precursor ≤ 1 µm.

3. The negative electrode active material according to claim 1, wherein the average misorientation angle of the silicon-based grains is 5° or more.

4. The negative electrode active material according to claim 1, wherein the silicon-based active material contains one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and relative to 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) is 70 parts by weight or more.

5. A silicon precursor, the silicon precursor contains a composition satisfying the following formulas 3 and 4: [Formula 3] 10 µm ≤ plate thickness of the silicon precursor ≤ 2 mm [Formula 4] 2 nm ≤ grain size of the silicon precursor ≤ 1 µm.

6. A method for manufacturing a negative electrode active material, the method comprising: Performing a rapid cooling process on metallic silicon to form a silicon precursor; and Pulverizing the silicon precursor to form a silicon-based active material, wherein the rapid cooling process of the metallic silicon is carried out by any one of melt spinning, suction casting, and injection casting.

7. The method according to claim 6, the method further comprising heating the metallic silicon by an induction furnace before the rapid cooling process of the metallic silicon.

8. The method according to claim 6, wherein: After forming the silicon precursor by the rapid cooling process of the metallic silicon, the silicon precursor contains a composition satisfying the following formulas 3 and 4: [Formula 3] 10 µm ≤ plate thickness of the silicon precursor ≤ 2 mm [Formula 4] 2 nm ≤ grain size of the silicon precursor ≤ 1 µm.

9. The method according to claim 6, wherein: After forming the silicon-based active material by pulverizing the silicon precursor, the silicon-based active material contains a composition satisfying the following formulas 1 and 2: [Formula 1] 1 µm ≤ particle size (D50) of the silicon-based active material ≤ 10 µm [Formula 2] 2 nm ≤ grain size of the silicon-based active material ≤ 100 nm.

10. A negative electrode composition, the negative electrode composition comprising: The negative electrode active material according to any one of claims 1 to 4; A negative electrode conductive material; and A negative electrode binder.

11. The negative electrode composition according to claim 10, wherein relative to 100 parts by weight of the negative electrode composition, the negative electrode active material accounts for 40 parts by weight or more.

12. The negative electrode composition according to claim 10, wherein the negative electrode conductive material contains a planar conductive material and a linear conductive material.

13. A negative electrode for a lithium secondary battery, the negative electrode comprising: A negative electrode current collector layer; and A negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer, The negative electrode active material layer comprises the negative electrode composition according to claim 10 or a cured product of the negative electrode composition according to claim 10 . 14 . The negative electrode for a lithium secondary battery according to claim 13 , wherein the thickness of the negative electrode current collector layer is 1 μm to 100 μm, and The thickness of the negative electrode active material layer is 5 μm to 500 μm.

15. A lithium secondary battery, comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 13; A separator disposed between the positive electrode and the negative electrode; and Electrolytes.

16. A method for manufacturing a negative electrode active material, the method comprising: preparing molten metallic silicon; Performing a rapid cooling process on the molten metal silicon to form a plate-shaped metal silicon precursor; Determining whether the plate thickness of the metal silicon precursor is 10 μm to 2 mm and whether the grain size of the metal silicon precursor is 2 nm to 1 μm; When the plate thickness and grain size of the metal silicon precursor are determined to be 10 μm to 2 mm and 2 nm to 1 μm, respectively, pulverizing the metal silicon precursor to form a silicon-based active material; determining whether the particle size (D50) of the formed silicon-based active material is 1 µm to 10 µm and whether the grain size of the formed silicon-based active material is 2 nm to 1 µm; and When the particle size (D50) and the grain size of the silicon-based active material are determined to be 1 μm to 10 μm and 2 nm to 1 μm, respectively, the silicon-based active material is classified as an active material for manufacturing a negative electrode for a lithium secondary battery.

17. The method according to claim 16, wherein the rapid cooling process is performed by any one of melt spinning, suction casting and injection casting.

Citation Information

Patent Citations

  • Apparatus for controlling motor and method for controlling motor thereof

    KR1020230052006A